ON SOME PROBLEMS OF DEVELOPMENT OF THE TOURISM INDUSTRY IN ROSTOV REGION, RUSSIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The purpose of this work is to analyze current problem areas in the development of tourism in the Rostov Region of the Russian Federation to determine the vector of further development of the industry. The main sources of the work were published program documents and research by experts from previous years. The following methods were used: empirical, logical analysis, generalization, synthesis.
Keywords: tourism; tourism industry; cultural tourism; enogastronomy; tourist routes; infrastructure; tourism development